1996
DOI: 10.1007/bf00141703
|View full text |Cite
|
Sign up to set email alerts
|

Modeling carbon stores in Oregon and Washington forest products: 1900?1992

Abstract: A new model, FORPROD, for estimating the carbon stored in forest products, considers both the manufacture of the raw logs into products and the fate of the products during use and disposal. Data for historical patterns of harvest, manufacturing efficiencies, and product use and disposal were used for estimating the accumulation of carbon in Oregon and Washington forest products from 1900 to 1992. Pools examined were long-and short-term structures, paper supplies, mulch, open dumps, and landfills. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 40 publications
2
46
1
Order By: Relevance
“…Results from this study suggested that extending the half-life of PW products had only a marginal effect on C stock. Similar results were reported in other studies [14,56,58]. The ex situ C pools could be influenced by both the final utilization of particular products, and also by substituting wood for more C intensive materials.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results from this study suggested that extending the half-life of PW products had only a marginal effect on C stock. Similar results were reported in other studies [14,56,58]. The ex situ C pools could be influenced by both the final utilization of particular products, and also by substituting wood for more C intensive materials.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, all the product types were divided into four life span categories (Table 2) [12,56] and adapted to loblolly pine utilization patterns in the southeastern U.S. [57][58][59][60]. …”
Section: Ex Situ Wood Products Poolsmentioning
confidence: 99%
“…Similarly, the use of harvested biomass for the production of long-lasting products retains carbon for long periods of time [66,67]. There are records of carbon capture in managed forests that exceed the results obtained in this study.…”
Section: Carbon Sequestrationcontrasting
confidence: 56%
“…Because the latter likely replaces fossil fuels that would have been used anyway we do not consider this an additional loss of C associated with development per se, and use 30% over 90 years as a lower bound of AGB loss. For an upper bound, we use an estimate of 77% loss (Harmon et al, 1996). Thus we assume that 40 -222 Mg·C·ha -1 , less the amount of biomass still on the cleared portion of the house lot, are lost to the atmosphere in the 90 years after house development.…”
mentioning
confidence: 99%
“…Thus we assume that 40 -222 Mg·C·ha -1 , less the amount of biomass still on the cleared portion of the house lot, are lost to the atmosphere in the 90 years after house development. We use 90 years as a time frame because it is appropriate for this study (the oldest house is ~90 years) and because both Heath et al (1996) and Harmon et al (1996) give aggregate emissions estimates based on C fate in forest products over this time period, since the collection period of the harvest data from the Forest Service was .Biomass on each house lot was calculated by measuring diameter at breast height (DBH) for all trees on the site and using a generic allometric equation to determine biomass (Jenkins et al, 2004):Above Ground Biomass Exp B B lndbh  where B 0 = -2.4800 and B 1 = 2.4835; these parameters are mean values for mixed hardwoods (most house lots contained a broad mix of native softwoods and non-native planted hardwoods). While these parameters are meant specifically for trees growing in a canopied forest, using other common estimates for B 0 and B 1 in this type of system resulted in changes of <5 Mg·C·ha -1…”
mentioning
confidence: 99%